Reaction of Human Monoclonal Antibodies to SARS-CoV-2 Proteins With Tissue Antigens: Implications for Autoimmune Diseases - Vojdani, Aristo; Vojdani, Elroy; Kharrazian, Datis (Frontiers in Immunology, 2021)
We sought to determine whether immune reactivity occurs between anti-SARS-CoV-2 protein antibodies and human tissue antigens, and whether molecular mimicry between COVID-19 viral proteins and human tissues could be the cause. We applied both human monoclonal anti-SARS-Cov-2 antibodies (spike protein, nucleoprotein) and rabbit polyclonal anti-SARS-Cov-2 antibodies (envelope protein, membrane protein) to 55 different tissue antigens. We found that SARS-CoV-2 antibodies had reactions with 28 out of 55 tissue antigens, representing a diversity of tissue groups that included barrier proteins, gastrointestinal, thyroid and neural tissues, and more. We also did selective epitope mapping using BLAST and showed similarities and homology between spike, nucleoprotein, and many other SARS-CoV-2 proteins with the human tissue antigens mitochondria M2 and F-actin. This extensive immune cross-reactivity between SARS-CoV-2 antibodies and different antigen groups may play a role in the multi-system disease process of COVID-19, influence the severity of the disease, precipitate the onset of autoimmunity in susceptible subgroups, and potentially exacerbate autoimmunity in subjects that have pre-existing autoimmune diseases. Very recently, various vaccines and human monoclonal antibodies were approved for use on patients with COVID-19. The human monoclonal antibodies used in this study are almost identical with these approved antibodies. While the cross-reaction shown in our study may raise some concerns about future autoimmune diseases, it cannot be denied that the approval of vaccines and human monoclonal antibodies with which to fight the current pandemic may not only save countless human beings from the multi-system disorders of COVID-19, but will also ease the fears that have gripped a terror-stricken world.